U-shaped relationship between platelet–lymphocyte ratio and postoperative in-hospital mortality in patients with type A acute aortic dissection - Xi Xie (BMC, 2021)
Abstract Background The platelet-lymphocyte ratio (PLR), a novel inflammatory marker, is generally associated with increased in-hospital mortality risk. We aimed to investigate the association between PLR and postoperative in-hospital mortality risk in patients with type A acute aortic dissection (AAAD). Methods Patients (n = 270) who underwent emergency surgery for AAAD at Xiangya Hospital of Central South University between January 2014 and May 2019 were divided into three PLR-based tertiles. We used multiple regression analyses to evaluate the independent effect of PLR on in-hospital mortality, and smooth curve fitting and a segmented regression model with adjustment of confounding factors to analyze the threshold effect between PLR and in-hospital mortality risk. Results The overall postoperative in-hospital mortality was 13.33%. After adjusting for confounders, in-hospital mortality risk in the medium PLR tertile was the lowest (Odds ratio [OR] = 0.20, 95% confidence interval [CI] = 0.06–0.66). We observed a U-shaped relationship between PLR and in-hospital mortality risk after smoothing spline fitting was applied. When PLR < 108, the in-hospital mortality risk increased by 10% per unit decrease in PLR (OR = 0.90, P = 0.001). When the PLR was between 108 and 188, the mortality risk was the lowest (OR = 1.02, P = 0.288). When PLR > 188, the in-hospital mortality risk increased by 6% per unit increase in PLR (OR = 1.06, P = 0.045). Conclusions There was a U-shaped relationship between PLR and in-hospital mortality in patients with AAAD, with an optimal PLR range for the lowest in-hospital mortality risk of 108–188. PLR may be a useful preoperative prognostic tool for predicting in-hospital mortality risk in patients with AAAD and can ensure risk stratification and early treatment initiation.